Sustainability Status of The Ecological Dimension in The Fisheries Management of Bali Sardine (Sardinella lemuru Bleeker 1853) in The Bali Strait - Noar Muda Satyawan; Yulia Estmirar Tanjov; Agus Purwanto; Made Mahendra Jaya; Liya Tri Khikmawati; Wulandari Sarasati; Muth Mainnah; Muh. Arkam Azis; Aditya Bramana (Jurnal Biologi Tropis, 2023)
Bali Strait included in the 573 Fisheries Management Area of Indonesia. One of the dominant commodities in these waters were Bali sardine (Sardinella lemuru). The dynamics of the lemuru fishery in the Bali Strait is fluctuating and tends to decrease. This study aims to determine the sustainability status of the ecological dimensions in the fisheries management of Bali sardine in the Bali Strait. Survey method were used in this study to obtain primary and secondary data related to ecological dimension attributes and then analyzed using the RAPFISH (Rapid Apraisal Technique for Fisheries) method. The results of this study indicate that the ecological dimension of lemuru fishery management in the Bali Strait has an index of 44.03 (less sustainable). There are three sensitive attributes that affect the sustainability of the ecological dimension, there were the level of utilization of fish resources, size of fish caught, and the number of catches. The recommended improvements for the sustainability of the ecological dimension were limiting fishing quotas, limiting the mesh size of fishing gear, and limiting areas and fishing seasons.